Presidential Address to the Geological Association of Canada, Toronto, Ontario:: Base Metal Deposits in Sedimentary Rocks: Some Approaches - Macqueen, R. (Geoscience Canada, 1979)
Abstract To consider both the deposits and their setting within a sedimentary basin is an instructive and rewarding approach in studying Mississippi Valley-type lead-zinc deposits hosted by sedimentary carbonate rocks. There are now numerous constraints on origin of these deposits, and the sedimenary-diagenetic hypothesis of origin still appears to answer more questions than it poses. Oil in basins seems clearly related to the thermal and structural evolution of sedimentary basins. Ore, in comparison, appears to require coincidence of a specific set of precipitation as sulphides. Recognition of the importance of heat in the maturation of organic matter has led to the development of indices of thermal and organic maturity. It should be possible to apply these indices at least to relatively unde-formed Mississippi Valley-type deposits and their host rocks as a means of discovering burial and thermal history. Organic matter commonly is spatially associated with these deposits: a close look at such organic matter m the light of modern petroleum geochemistry should help to determine whether such association is casual, or genetic m terms of affecting source, transport and precipitation